Exercise as a therapy for sickle cell-associated musculoskeletal pain among children: Healthcare professionals’ perspectives - Britney Pinamang Gyampo; Isaac Mensah Bonsu (PLoS ONE, 2025)
Introduction Musculoskeletal (MSK) pain is one of the most substantial and debilitating complications of sickle cell disease (SCD), particularly in pediatric patients. Although exercise is recognized as a potential therapeutic strategy for managing SCD-associated MSK pain, the knowledge and attitudes of healthcare professionals regarding its use remain unclear. This study aimed to explore healthcare professionals’ perspectives on the role of exercise in managing MSK pain in children with SCD. Method Face-to-face semi-structured interviews were conducted with nineteen healthcare professionals (pediatric nurses and pediatricians). All interviews were transcribed verbatim; codes were generated and inductively organized into themes. Results Three major themes were identified that described healthcare professionals’ perspectives on using exercise as a therapy for MSK pain in children with SCD. These included understanding exercise in managing MSK pain in SCD, barriers to using exercise in managing MSK pain in SCD, and facilitators for implementing an exercise program for MSK pain in SCD. Conclusions Healthcare professionals acknowledge the potential benefits of exercise in managing musculoskeletal (MSK) pain in children with sickle cell disease (SCD); however, overcoming identified barriers and utilizing facilitators is essential for effective implementation.